1992
DOI: 10.1148/radiology.182.1.1727282
|View full text |Cite
|
Sign up to set email alerts
|

Nondisplaced fractures of the greater tuberosity of the humerus: sonographic detection.

Abstract: In this retrospective study, the sonographic appearance of fracture of the greater tuberosity of the humerus was evaluated in 17 men and 14 women aged 20-69 years with acute, semiacute, or remote shoulder trauma in whom results of rotator cuff sonography had suggested the diagnosis of such a fracture. Clinical data, radiologic reports, sonograms, and initial plain radiographs of the shoulder were analyzed; clinical follow-up information was assessed in 22 patients. Sonography showed discontinuity and irregular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
1
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(51 citation statements)
references
References 0 publications
2
46
1
2
Order By: Relevance
“…Also, Hollister et al [10] showed that sonographically detected subac romial and subdeltoid fluid, especially when combined with ajoint effusion, is highly spe cific and has a high positive predictive value for rotator cuff tears.Although correlative ra diographs were available for only 12 subjects, our results suggestthat the greater tuberosity is more readily defined by sonography than by conventional radiography. This finding was also indicated by Patten et al [4], who showed that of 24 greater tuberosity fractures detectedby sonography, 10 were missedby conventional radiography. It has been unclear whether abnormal greater tuberosities were due to aging or to as sociatedrotator cuff tears.Our results suggest that after accounting for age, a statistically sig nificant correlation exists betweenrotator cuff tearsand greater tuberosity irregularity.…”
Section: Blongitudinal Sonogram Through Leftsupraspinatus Tendonshowsupporting
confidence: 64%
See 1 more Smart Citation
“…Also, Hollister et al [10] showed that sonographically detected subac romial and subdeltoid fluid, especially when combined with ajoint effusion, is highly spe cific and has a high positive predictive value for rotator cuff tears.Although correlative ra diographs were available for only 12 subjects, our results suggestthat the greater tuberosity is more readily defined by sonography than by conventional radiography. This finding was also indicated by Patten et al [4], who showed that of 24 greater tuberosity fractures detectedby sonography, 10 were missedby conventional radiography. It has been unclear whether abnormal greater tuberosities were due to aging or to as sociatedrotator cuff tears.Our results suggest that after accounting for age, a statistically sig nificant correlation exists betweenrotator cuff tearsand greater tuberosity irregularity.…”
Section: Blongitudinal Sonogram Through Leftsupraspinatus Tendonshowsupporting
confidence: 64%
“…The greater tuberosity can also be imaged well (Fig. 1); one paperdescribesradiographically occult traumatic changes to the greater tuber osity that appearedto be a fracture on sono graphy [4]. Irregularities in the greater tuberosity have never been formally corre lated with rotator cuff tears, although the relationshiphasbeensuggested in the ortho pedic literature, in a pathologic study of the tendon-bone junction, and in one prior report on shoulder radiographs [5â€"71.…”
mentioning
confidence: 99%
“…In a MR study [11], radiographically occult fractures of the greater tuberosity were found in 9 (38%) of 24 patients with clinically suspected traumatic tears of the rotator cuff. Finally, Patten et al [6] support the fact that if the greater tuberosity is not displaced, radiographs may not show the fracture, regardless of the number and angle of the views obtained.…”
Section: Introductionmentioning
confidence: 95%
“…41 The early use of MRI allowed for an accurate diagnosis of the fracture, which assisted the therapist and surgeon to structure a conservative treatment plan that would allow for adequate healing. The only nonimaging assessment that has been reported as clinically effective in identifying an isolated nondisplaced greater tuberosity fracture is the presence of tenderness on the lateral wall of the greater tuberosity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is important when diagnosing either greater or lesser tuberosity fractures to distinguish the fracture from a rupture of the corresponding musculature. 17 Both rotator cuff tears and fractures can produce similar complaints of pain and weakness in abduction, 41,51 making it difficult to distinguish these injuries based on history and physical examination alone. Ogawa et al 39 reported in 2003 that isolated greater tuberosity fractures continue to be easily overlooked.…”
mentioning
confidence: 99%